2013
DOI: 10.1371/journal.ppat.1003301
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Exploitation of Diverse Host Nutrients Enhances Salmonella Virulence

Abstract: Pathogen access to host nutrients in infected tissues is fundamental for pathogen growth and virulence, disease progression, and infection control. However, our understanding of this crucial process is still rather limited because of experimental and conceptual challenges. Here, we used proteomics, microbial genetics, competitive infections, and computational approaches to obtain a comprehensive overview of Salmonella nutrition and growth in a mouse typhoid fever model. The data revealed that Salmonella access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
199
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(208 citation statements)
references
References 98 publications
9
199
0
Order By: Relevance
“…However, comparison of the Shigella data with our recent study on Salmonella enterica metabolism in a mouse typhoid fever model (37) reveals commonalities and striking differences. Shigella, like Salmonella and many other pathogens (37), exploits the fact that most biomass components are readily available in infected host environments. Uptake of these biomass components can save substantial biosynthesis costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparison of the Shigella data with our recent study on Salmonella enterica metabolism in a mouse typhoid fever model (37) reveals commonalities and striking differences. Shigella, like Salmonella and many other pathogens (37), exploits the fact that most biomass components are readily available in infected host environments. Uptake of these biomass components can save substantial biosynthesis costs.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of these biomass components can save substantial biosynthesis costs. However, Shigella has access to a high-flux supply for pyruvate that provides sufficient energy to drive fast growth, whereas intracellular Salmonella has access to many diverse but only scarce energy sources that together just support slow nutrient-limited growth (37). This striking difference may reflect the fact that Shigella reside directly in the host cytoplasm, whereas intracellular Salmonella are surrounded by a phagosomal membrane with apparently poor permeability in macrophages (their main target cell type during systemic infections).…”
Section: Discussionmentioning
confidence: 99%
“…This may slow down the growth but does not affect survival and therefore leave little scope for the development of resistance. Metabolism associated genes of pathogens have been consistently linked with virulence of major pathogens, [1][2][3][4][5][6][7][8][9] such as, role of carbon metabolism related pathways like glycolysis 10 and TCA cycle 11 in virulence of Salmonella Typhimurium and requirement of metabolism associated pathways for protection of Mycobacterium tuberculosis from host immune system. 9 Salmonella is even known to modulate host to exploit the limited supply of nutrients.…”
Section: Potential Of Peptide Transporters In Antimicrobial Therapymentioning
confidence: 99%
“…9 Salmonella is even known to modulate host to exploit the limited supply of nutrients. 8,12 Coupling of nutrition with virulence reveals metabolism associated genes that can be targeted for antimicrobial therapy. Peptide transporters represent one such class of genes known to be required for virulence of Gram negative as well as Gram positive pathogens.…”
Section: Potential Of Peptide Transporters In Antimicrobial Therapymentioning
confidence: 99%
“…The network revealed a wide-ranging distribution of CovS-regulated genes in pathways relevant to nutritional derivation. By examining nutritional genes at the genome-wide scale, we found that the nutritional derivation of pathogenic GAS is highly redundant and that many nutrients can be supplied by multiple genetic loci or physical sources with regard to extracellular nutrient uptake or de novo biosynthesis (55). As examples, two loci for ␤-glucoside transport were simultaneously downregulated by CovS ϩ at LP and upregulated at SP and de novo biosynthesis of cysteine and the cysteine transporter system were both upregulated at SP by CovS ϩ .…”
Section: Validation Of Regulated Virulence Genes By Q-rt-pcrmentioning
confidence: 99%